Gender differences in glaucoma - S. A. Zubasheva; I. R. Gazizova; A. V. Seleznev; Yu. I. Razhko; A. Yu. Brezhnev; A. V. Kuroyedov (Российский офтальмологический журнал, 2021)
The review analyzes current literature data on the relationship between gender and glaucoma incidence, and assesses the demographic and behavioral factors that may contribute to gender differences. Potential risks for the development and progression of glaucoma in men and women have been identified in numerous studies, the main ones being age, gender, and race. The prevalence of glaucoma in the world among people aged 40 to 80 years is higher than in other age groups and will grow steadily. Women are more likely to suffer from closed-angle glaucoma, while primary open-angle glaucoma is more common in men. Further genetic studies of this disease will provide a better understanding of the underlying pathomorphic  mechanisms and may improve therapeutic approaches in the future.  Individuals with the highest risk of developing glaucoma should be checked by an ophthalmologist in time for early detection and slowing the  progression of the disease.